Photocorrosion of Hematite Photoanodes in Neutral and Alkaline Electrolytes - Benavente Llorente, Victoria (2023)
Photoelectrochemical (PEC) water splitting is a promising energy conversion technology based on the harvesting of sunlight to produce green hydrogen. One of the major challenges hindering the development of PEC devices is the stability of photoanodes since most semiconductors are susceptible to anodic decomposition in aqueous solutions. While hematite (α-Fe2O3) has been regarded as one of the most stable metal oxides to drive the oxygen evolution reaction in alkaline media, its photostability in a broad pH range is poorly investigated. In this work, we study the dissolution of model Fe2O3 thin films in different electrolytes, including unbuffered and buffered neutral, near-neutral, and alkaline solutions, using on-line PEC inductively coupled plasma mass spectrometry. Fe leaching is observed in all studied unbuffered electrolytes under irradiation while phosphate-buffered electrolytes reveal a dramatic stability enhancement at all pHs. The latter might imply that phosphate buffers either alleviate local acidification in the close vicinity of the electrode-electrolyte interface during the reaction or that specific adsorption of phosphate anions at the α-Fe2O3 surface could mitigate dissolution. Furthermore, we explore the long-term stability of α-Fe2O3 using a three-electrode bulk PEC cell. In the long run, phosphate buffers do not represent an optimal electrolyte choice either, as the surface Fe oxide gradually converts to Fe phosphates that are not photoelectrochemically active. Our work demonstrates that photocorrosion of Fe2O3 within electrolytes that are commonly used in the literature is not negligible and should be considered for designing stable semiconductor interfaces.